The Effect of POC (Shame Plant Root LOM) and Coconut Water on Growth and Result of Pakcoy Plants (Brassica rapa L.) - Dela Kurniasari; Sigit Soeparjono (Berkala Ilmiah Pertanian, 2022)
Mustard pakcoy plant is one of the vegetables which is much in demand by society. For the sake of society's awareness of the importance of a healthy plant, it is necessary to develop healthier mustard pakcoy plants. That effort can be done by taking the advantages of organic materials such as organic fertilizer, a natural hormone, organic pesticides, and so on. This research aimed to find out the productivity improvement of mustard pakcoy plants by applying LOF (shame plant root LOM) and coconut water. This research was conducted in Antirogo Village Sumbersari District Jember Regency starting from May 2019 to July 2019. The method used in this research was a 2-factor-Completely Randomized Design (CRD) factorial in the design with 3-time repetitions. The first factor, 4 concentration levels of shame plant LOM, the second factor, 3 concentration levels of coconut water, so the total number of plants used is 36 plants. Data obtained was analyzed using ANOVA and if there was a significant or highly significant difference of treatment effect, the advanced test was conducted by using Duncan's multiple range test (DMRT) at the level of 95%. Based on the research results, it showed that the application of LOF (shame plant LOM) and coconut water had a highly significant effect on the parameter of fresh weight of the plant with the total weight of 645.15 gr/plant, while the single factor of the application of LOF (shame plant LOM) and coconut water had a significant effect on the parameter of plant height, number of leaves, chlorophyll content. At the single factor of coconut water treatment, it had a significant effect on the N networks.